THE ROLE OF ISLAMIC BANKING IN DEVELOPING SHARIA FINTECH IN INDONESIA - Alfania Cahaya Kamila (SHACRAL: Shari'ah Economics Review Journal, 2024)
The rapid development of financial technology (fintech) has significantly transformed the global financial services industry, including Islamic finance. In Indonesia, the expansion of sharia fintech presents a strategic opportunity to strengthen financial inclusion and accelerate the growth of the Islamic economy. Islamic banking institutions, as formal financial intermediaries operating under sharia principles, play a crucial role in supporting the development of sharia fintech through capital provision, infrastructure integration, regulatory compliance, and market access. This study aims to examine the role of Islamic banking in fostering sharia fintech development in Indonesia using a qualitative approach based on secondary data. The research employs a comprehensive literature review of academic journal articles, regulatory documents, and official reports published by national and international institutions such as the Financial Services Authority (OJK), Bank Indonesia, and Statistics Indonesia (BPS). The findings indicate that Islamic banks contribute to sharia fintech development in several strategic ways: acting as funding partners for fintech startups, providing payment and settlement infrastructure, ensuring sharia compliance through supervisory mechanisms, and expanding outreach to underserved communities and micro, small, and medium enterprises (MSMEs). However, the study also identifies several challenges, including limited digital capabilities of Islamic banks, regulatory gaps specific to sharia fintech governance, issues related to digital sharia compliance, and relatively low levels of Islamic financial literacy. Empirical data show that although internet penetration and digital financial adoption in Indonesia continue to rise, the level of inclusive access to sharia-based digital financial services remains uneven. This article argues that stronger collaboration between Islamic banks, fintech firms, and regulators is essential to create a sustainable sharia fintech ecosystem. The study offers policy and managerial recommendations to enhance digital transformation, regulatory harmonization, and financial literacy initiatives, contributing to the long-term development of Indonesia’s Islamic financial sector.